Earnings quality, Corporate governance, Corporate restructuring of the special treatment firms in China - XIONG, JIAQI (2016)
This study is conducted under the Chinese institutional background and reviews the evolution of the special treatment regulation mandated by the CSRC. This exceptional policy creates a very special part in Chinese stock market and this special treatment stock is to be suspicious of various earnings manipulation. Different from prior empirical study, this study employs the special treatment firms as sample to comprehensively investigate the effect of an accounting number-based policy on financial reporting quality, corporate restructuring activities and corporate governance. The analysis of findings also takes both traditional theories and recent empirical findings into consideration. At the end, limitation of this study and possible implications for standard setter are provided.